MAXIMUM ADVANCE OF THE SCANDINAVIAN ICE SHEET ONTO THE SHELF OF THE BARENTS SEA IN VALDAY TIME - Dunayev N.N.; Levchenko O.V.; Merklin L.R.; Pavlidis Yu.A. (My University, 1989)
The scale of manifestation of the Valday glaciation in the northern shelf zones of Eurasia continues to be controversial. This problem is of both theoretical and practical importance. It is particularly important in planning various economic objectives involving navigation, fisheries, engineering geology, and prospecting. The authors investigations in the region of the Arctic islands indicate that ice breaks off from present-day shelf glacier near the ice edges. Thawing of the glacial ice fragments and small icebergs also largely takes place near the glacier. The farthest northward advance of the glacier onto the Barents Sea apparently did not exceed 71° N. The Pay-Khoy and Novaya Zemlya glaciers were not joined during the Valday time. The reason why such large areas of the shelf covered by sheet glaciation are reported in the literature seems to be that in echo soundings, the relief of the subjacent sedimentary rock often looks like moraine relief. Only continuous seismo-acoustic profiling can distinguish the areal extent and types of the unconsolidated structures and thus give more detail on the paleogeographic situation during the late Quaternary.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная